Alumina-forming austenitic-ferritic stainless steel alloy

CN122941963APending Publication Date: 2026-10-20合瑞迈欧洲中东和非洲有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611143303.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-06-01
Filing Date
2022-05-31
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,所公开的组成的抗氧化性在500至900℃之间的温度下是不足的

Benefits of technology

[0011]本公开内容还提供了一种包含具有如上文或下文所限定的微观结构的奥氏体-铁素体不锈钢组成的物体。本发明的不锈钢将使得能够在所述物体上形成氧化铝层,这将使所述物体能够在500-900℃的温度范围内在具有宽范围的氧气浓度的气氛中使用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This disclosure relates to an alumina-forming austenitic-ferritic stainless steel alloy. It also relates to a method of manufacturing an alumina-forming austenitic-ferritic stainless steel object. Furthermore, this disclosure relates to a product and its use in a temperature range of 500 to 900°C.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention patent application is a divisional application of Chinese invention patent application No. 202280036710.2, filed on May 31, 2022, entitled "Alumina-forming austenitic-ferritic stainless steel alloy". Technical Field

[0002] This disclosure relates to an austenitic-ferritic stainless steel alloy. More specifically, this disclosure relates to an alumina-forming austenitic-ferritic stainless steel alloy. This disclosure also relates to a method of manufacturing an alumina-forming austenitic-ferritic stainless steel object, a product comprising the alumina-forming austenitic-ferritic stainless steel, and the use of the object in a particular environment. Background Technology

[0003] Existing technologies disclose examples of duplex stainless steels comprising austenitic and ferritic phases, which, when subjected to an oxygen-containing atmosphere at high temperatures, are capable of forming a protective alumina layer on their surface. Such duplex stainless steels typically contain high levels of nickel, chromium, and aluminum.

[0004] Wang et al., “Effects of carbon and chromium on the solidification structure and properties of ferrite-austenite duplex heat-resistant alloy,” *Science and Technology of Advanced Materials*, Elsevier Science, Vol. 2, No. 1, July 30, 2001, pp. 297-302, disclose a ferrite-austenite duplex alloy tested in air at 1250 °C. However, these alloys have drawbacks, including insufficient oxidation resistance at temperatures between 500 and 900 °C. Furthermore, some of these alloys exhibit excessive brittleness, resulting in excessively low ductility for conventional manufacturing methods.

[0005] Hyunmyung et al., “Development of alumina-forming duplex stainless steels as accident-tolerant fuel cladding materials for light water reactors,” Journal of Nuclear Materials, Elsevier Science, Vol. 507, April 21, 2018, pp. 1-14, disclose a high-alumina-content (>5 wt%) duplex stainless steel that underwent corrosion resistance testing under 1200 °C steam and simulated pressurized water reactor (PWR) operating conditions. However, the oxidation resistance of the disclosed composition is insufficient at temperatures between 500 and 900 °C.

[0006] Therefore, there is still a need in this technical field for an optimized austenitic-ferritic stainless steel alloy that would enable the manufacture of stainless steel-containing objects using conventional manufacturing methods and would provide objects with excellent oxidation resistance when used in a temperature range of 500 to 900°C. Summary of the Invention

[0007] Therefore, this disclosure provides an improved alumina-forming austenitic-ferritic stainless steel alloy composition having an optimized microstructure comprising austenite and ferrite, for use in a temperature range of 500 to 900°C.

[0008] The austenitic-ferritic stainless steel according to this disclosure is characterized in that the stainless steel comprises the following composition (in weight %): Cr 11.0 to 16.0; Ni 11.5 to 15.0; Al 3.5 to 5.0; C 0.01 to 0.15; Nb 0.01 to 2.0; Mn 0.01 to 3.5; Si 0.01 to 0.8; Cu 0 to 5.5; Zr 0 to 0.3; Mo+W 0 to 3.0; The balance consists of Fe and unavoidable impurities; The austenitic-ferritic stainless steel described therein has a microstructure comprising more than 15% by volume and less than 45% by volume of ferrite, with the remainder being austenite.

[0009] In this disclosure, the austenitic-ferritic stainless steel has a ferrite content ranging from greater than 15% by volume to less than 45% by volume, with the remainder being austenite, because this microstructure has been found to be crucial for oxidation resistance in a temperature range of 500 to 900°C. If the amount of ferrite is less than 15% by volume, it indicates that oxidation resistance and mechanical strength will decrease. If the ferrite content is greater than 45% by volume, it indicates that there will be problems with the formation of a protective oxide layer in the stainless steel of the present invention at temperatures above approximately 650°C.

[0010] This disclosure also provides a method for manufacturing an object comprising an austenitic-ferritic stainless steel having the microstructure defined above or below. The method for manufacturing this alloy follows conventional smelting metallurgical manufacturing methods, as it has been surprisingly found that the stainless steel of the present invention possesses sufficiently high thermal ductility to make this possible.

[0011] This disclosure also provides an object comprising an austenitic-ferritic stainless steel having the microstructure defined above or below. The stainless steel of the present invention will enable the formation of an alumina layer on said object, which will allow the object to be used in atmospheres with a wide range of oxygen concentrations within a temperature range of 500-900°C. Attached Figure Description

[0012] Figure 1a -b disclosed the results of oxidation tests at 800 and 900 °C, respectively.

[0013] Figure 2 A graph showing yield strength as a function of different heat treatments is disclosed. Detailed Implementation

[0014] This disclosure relates to an alumina-forming austenitic-ferritic stainless steel, characterized in that the alloy has the following composition (in weight %): Cr 11.0 to 16.0; Ni 11.5 to 15.0; Al 3.5 to 5.0; C 0.01 to 0.15; Nb 0.01 to 2.0; Mn 0.01 to 3.5; Si 0.01 to 0.8; Cu 0 to 5.5; Zr 0 to 0.3; Mo+W 0 to 3.0; The balance consists of Fe and commonly present impurities; Furthermore, the austenitic-ferritic stainless steel described therein has a microstructure comprising more than 15% by volume and less than 45% by volume of ferrite, with the remainder being austenite.

[0015] The alloying elements of steel according to this disclosure will now be described in more detail. The terms "weight%" and "wt%" are used interchangeably. Moreover, the list of properties or contributions mentioned for a particular element should not be considered exhaustive.

[0016] Iron (Fe) balance

[0017] The primary role of iron in austenitic-ferritic stainless steel is to balance the composition of the steel or the alloying elements. The balance also includes unavoidable impurities, which will be discussed later.

[0018] Chromium (Cr) 11.0 to 16.0% by weight

[0019] Cr is an important element because it is a ferrite stabilizer, thus helping to maintain a proper microstructure containing more than 15% by volume and less than 45% by volume of ferrite, with the remainder being austenite.

[0020] Cr also promotes the formation of aluminum oxide, i.e., an aluminum oxide layer, on the manufactured object through the so-called third element effect of forming chromium oxide during the transient oxidation phase. Particularly at temperatures in the range of 500-600°C, the formation of an aluminum oxide layer on the object may be hampered if the chromium content is insufficient. Furthermore, chromium is an important element because it improves corrosion resistance. Therefore, the minimum chromium content in the steel of the present invention is 11.0% by weight. According to one embodiment, the minimum chromium content is 12.0% by weight.

[0021] However, if the Cr content is too high, the ferrite content will become excessive, which will lead to reduced oxidation resistance, especially at higher temperatures such as 800 to 900 °C. Excessive Cr content can also lead to the formation of secondary phases, such as sigma phases, which will cause embrittlement. Therefore, the maximum chromium content is 16.0% by weight, such as a maximum of 15.5% by weight.

[0022] According to the embodiment, the Cr content is 11.0 to 16.0% by weight, such as 12.0 to 16.0% by weight, such as 12.0 to 15.5% by weight.

[0023] Nickel (Ni) 11.5 to 15.0% by weight

[0024] Ni is an important element because it acts as an austenite stabilizer, thus helping to maintain a proper microstructure. If the nickel content is too low, there is a risk of an excessive ferrite phase content, which will lead to a loss of oxidation resistance, especially at temperatures above 800°C. Furthermore, too little Ni will also cause austenite to transform into martensite at room temperature. Therefore, the minimum nickel content is 11.5% by weight.

[0025] On the other hand, if the amount of Ni is too high, the amount of ferrite will be too low, which will result in poor mechanical properties, such as low tensile strength.

[0026] Ni should also be balanced with the amount of aluminum added, as it will bind to aluminum in the form of nickel aluminum compounds, thereby inhibiting the formation of an alumina layer to some extent. However, nickel aluminum compounds can provide improved mechanical properties in the manufactured object, such as increased hardness and improved yield strength. To some extent, nickel can be replaced by cobalt (Co). However, since Co is less preferred from an environmental perspective, Ni is preferred. Therefore, the maximum Ni content is 15.0% by weight. According to embodiments, the Ni content is 11.5 to 15.0% by weight, such as 12.0 to 14.5% by weight.

[0027] Aluminum (Al) 3.5 to 5.0% by weight

[0028] Al is also an important element in the steel of this invention because when exposed to oxygen at high temperatures, Al will form a dense and thin layer of aluminum oxide on the manufactured object, which will protect the underlying surface from further oxidation. If the Al content is too low, when the steel is subjected to an oxygen-containing atmosphere at elevated temperatures such as 500-900°C, it will limit the formation of a sufficiently thick protective alumina layer or prevent the formation of a sufficiently thick protective alumina layer. Furthermore, Al will form nickel aluminum compounds with Ni, thereby contributing to increased hardness. Therefore, the minimum aluminum content is 3.5% by weight.

[0029] Furthermore, Al is a ferrite stabilizer, thus helping to maintain a proper microstructure. If the amount of Al is too high, the ferrite content becomes excessive, leading to reduced oxidation resistance, especially at temperatures such as 800 to 900°C. Therefore, the maximum content of aluminum is 5.0% by weight. According to embodiments, the Al content is 3.5 to 5.0% by weight, such as 3.7 to 4.9% by weight.

[0030] Carbon (C) 0.01 to 0.15% by weight

[0031] Carbon (C) will form carbides with many elements present in the austenitic-ferritic stainless steel, thereby contributing to increased hardness and strength (e.g., creep properties) of the steel. Furthermore, C is also an austenite stabilizer. Therefore, the minimum carbon content is 0.01% by weight, such as 0.03% by weight. Excessive carbon content will increase the risk of forming excessive carbides, such as M... 23 C6 and / or M7C3 carbides will reduce antioxidant properties. Therefore, the maximum carbon content is 0.15% by weight, such as 0.13% by weight. According to the embodiment, the C content is 0.01 to 0.15% by weight, such as 0.03 to 0.13% by weight.

[0032] Niobium (Nb) 0.01 to 2.0% by weight

[0033] Nb is a ferrite stabilizer, thus helping to maintain a proper microstructure.

[0034] Furthermore, Nb will form niobium carbides together with C, thereby inhibiting the excessive formation of chromium carbides, which may negatively affect the formation of the alumina layer. Therefore, the minimum Nb content is 0.01% by weight. According to one embodiment, the minimum Nb content is 0.05% by weight.

[0035] However, excessive Nb will lead to the formation of excessive niobium carbides, which will cause the steel to become brittle. Therefore, the maximum niobium content is 2.0% by weight, such as a maximum of 1.50% by weight. According to the embodiment, the Nb content is therefore from 0.01 to 2.0% by weight, such as from 0.05 to 1.60% by weight, such as from 0.05 to 1.60% by weight.

[0036] Manganese (Mn) 0.01 to 3.5% by weight

[0037] Manganese (Mn) is an austenitic stabilizer and can replace nickel to some extent without compromising its antioxidant properties. Therefore, the maximum Mn content is 3.5% by weight, such as a maximum of 3.2% by weight. According to embodiments, the Mn content is from 0.01 to 3.5% by weight, such as 0.01 to 3.2% by weight, such as 0.05 to 3.1% by weight.

[0038] Silicon (Si) 0.01 to 0.8% by weight

[0039] Si is added to improve antioxidant properties. Therefore, the minimum Si content is 0.01 wt%. However, excessive Si may increase the risk of sigma phase formation. Therefore, the maximum silicon content is 0.8 wt%. According to one embodiment, the maximum Si content is 0.7 wt%, such as 0.6 wt%. According to another embodiment, the Si content is 0.01 to 0.8 wt%, such as 0.01 to 0.7 wt%, such as 0.01 to 0.6 wt%.

[0040] Copper (Cu) 0 to 5.5% by weight

[0041] Cu can be optionally added or can be considered an impurity. If added intentionally and for the desired effect, the minimum content is 0.5% by weight. Cu can have a positive effect on the formation of nickel aluminides, which can provide improved mechanical properties such as improved hardness and yield strength. However, excessive Cu will result in an excess of nickel aluminides, which will reduce the thermal ductility of the object during manufacturing. For these reasons, the maximum Cu content is 5.5% by weight, such as 5.3% by weight, such as 5.2% by weight. According to embodiments, the Cu content is 0 to 5.5% by weight. According to embodiments, the Cu content is 0 to less than 0.5% by weight or 0.5 to 5.5% by weight.

[0042] Zirconium (Zr) 0 to 0.3% by weight

[0043] Zr can be optionally added or can be considered an impurity. If intentionally added, the minimum content is 0.05% by weight. Zr, together with carbon and nitrogen, forms zirconium carbonitrides, thereby inhibiting the formation of aluminum nitrides and chromium carbides, which in turn inhibits the formation of an alumina layer. However, excessive Zr leads to reduced hot ductility of the steel and difficulty in hot working. For this reason, the maximum Zr content is 0.3% by weight. According to embodiments, the Zr content is 0 to less than 0.05% by weight or 0.05 to 0.3% by weight.

[0044] Molybdenum (Mo) and / or tungsten (W) 0 to 3.0% by weight

[0045] Mo and W are considered equivalent elements and may be added optionally. Mo and / or W will combine with carbon by forming corresponding carbides, thereby reducing the amount of chromium carbides formed. However, excessive Mo and W may increase the risk of introducing intermetallic phases, such as Laves and sigma phases. For these reasons, the total content of W and Mo should therefore be limited to a maximum of 3.0% by weight.

[0046] Rare earth metals (REM) 0 to 0.1% by weight

[0047] REMs such as La, Ce, Y, Pr, and Sm can be optionally added. These elements are strong sulfide forming agents, thereby removing sulfur (S) from the steel, thus improving hot ductility, and can be present in amounts up to 0.1% by weight. Above this level, in combination with the Cu and Ni contents defined in this disclosure, REMs tend to have a negative impact on hot ductility.

[0048] Furthermore, hafnium (Hf), tantalum (Ta), and titanium (Ti) are considered functionally equivalent to elements Zr and Nb, and therefore can exist in the same amounts as those specified for these elements, and can partially or completely replace these elements.

[0049] In this document, phosphorus (P) and sulfur (S) can be considered as commonly present impurities. Phosphorus (P) can be accepted in the alloy at low levels. According to one embodiment, P ≤ 60 ppm. Sulfur (S) can be accepted in the alloy at low levels. According to one embodiment, S ≤ 60 ppm. According to one embodiment, P + S ≤ 60 ppm.

[0050] Nitrogen (N) is considered a commonly present impurity. According to one embodiment, the N content is ≤0.02% by weight.

[0051] Other impurities may also be present in austenitic-ferritic stainless steels as defined above or below. These impurities are generally unavoidable due to manufacturing processes, such as their presence in scrap metal melted to produce the steel composition of the present invention.

[0052] Alternatively, such elements, even if technically removeable from the melt, do not impair the functionality of the finished steel, such that there is no technical or economic incentive to undertake the work required to remove them. According to one embodiment that can be combined with all other embodiments mentioned in this disclosure, the maximum content of the typically present impurities does not exceed 0.5% by weight.

[0053] Furthermore, the austenitic-ferritic stainless steel as defined above or below may include any of the elements mentioned herein within any scope. According to one embodiment, the austenitic-ferritic stainless steel of the present invention comprises all the elements mentioned herein within any scope.

[0054] This disclosure also relates to a method for manufacturing austenitic-ferritic stainless steel objects using an austenitic-ferritic stainless steel composition as defined above or below, the method comprising the following steps: a) Provide an alumina-forming austenitic-ferritic stainless steel melt having an alloying element composition as defined above or below.

[0055] b) Cool the alumina-forming austenitic-ferritic stainless steel melt into a solid.

[0056] c) The solid is heat-processed into a workpiece of a predetermined shape at a temperature between 1000 and 1300°C.

[0057] The hot working step must be performed at a temperature above 1000°C; otherwise, the formation of intermetallic compounds will reduce ductility. According to the embodiment, the hot working temperature is above 1100°C. Above 1300°C, the risk of initial melting may lead to cracking in the bulk.

[0058] According to one embodiment, the heat treatment step can be repeated multiple times to obtain a workpiece of the desired shape.

[0059] According to one embodiment, the hot working step may include forging or hot rolling.

[0060] d) Heat-treat the workpiece at a temperature between 1050°C and 1200°C for approximately 2 to 120 minutes.

[0061] The time and temperature of the heat treatment steps will depend on the size and volume of the workpiece. However, in order to decompose any intermetallic phases, the temperature must be at least 1050°C, such as at least 1100°C. Moreover, the ferrite content will increase, and the extent of the increase will depend on the heat treatment temperature, so the maximum temperature is 1200°C, such as 1170°C, such as 1150°C, in order to obtain a suitable microstructure containing austenite and ferrite.

[0062] e) Quench the heat-treated workpiece to approximately room temperature.

[0063] The quenching can be performed by cooling the workpiece to approximately room temperature using air, water, or an oil bath.

[0064] According to one embodiment, an optional cold working step can be performed after at least one hot working step c) to obtain a workpiece with a predetermined shape and finer tolerances.

[0065] According to one embodiment, an optional aging step may be performed after the quenching step e). This aging step is carried out at a temperature above 500°C, such as 650 to 850°C, for a maximum of 240 hours, and for a maximum of 100 hours, to achieve age hardening effects, such as increased yield strength of the final object. During this aging step, no harmful secondary phases, such as sigma or Lavres phases, will form. However, room temperature (RT) ductility may decrease slightly after the aging step.

[0066] Furthermore, articles made of austenitic-ferritic stainless steel as defined above or below may contain any of the austenitic-ferritic stainless steel alloying elements mentioned herein within any scope. According to one embodiment, the austenitic-ferritic stainless steel articles of the present invention consist of all the alloying elements mentioned herein within any scope.

[0067] The final object can be of any shape, such as, but not limited to, tubes, strips, sheets, or wires. The object will have excellent oxidation resistance, good weldability, and mechanical properties that enable it to be used in non-pressurized applications, such as, but not limited to, muffle tubes, co-current heat exchanger tubes, and high-temperature heat exchangers.

[0068] Therefore, this disclosure also relates to the use of alumina-forming austenitic-ferritic stainless steel objects, as defined above or below, in applications where the objects are subjected to temperatures in the range of 500-900°C and in low-oxygen atmospheres. Examples of such applications are muffle tubes, co-current heat exchanger tubes, and high-temperature heat exchangers.

[0069] The following non-limiting experiments further illustrate the contents of this disclosure.

[0070] Example

[0071] Sample preparation

[0072] Prepare 14 alumina-forming austenitic-ferritic stainless steel melts with compositions disclosed in Table 1. Labeled with " The hot melt is a comparative example and therefore outside the scope of this invention.

[0073] All melts except 068 were prepared by melting in an induction furnace in an open atmosphere. 068 was prepared by induction melting (VIM) in a vacuum and then the melt was cooled into a solid.

[0074] The solid was cast into a 9-inch ingot and then forged at a temperature between 1180 and 1280°C. The sample has 50... The size is 120mm.

[0075] The forged ingot is then heat-treated at 1100°C for 20 minutes and quenched in water to approximately room temperature.

[0076] The sample was mechanically prepared by hot rolling, reducing its diameter from 50 mm to 15 mm.

[0077] After hot rolling, the sample was annealed at approximately 1130°C for 20 minutes.

[0078] The ferrite and austenite content of the annealed samples was measured using a 30-field grid with 100 points according to ASTM E562. Measurements were performed using an optical microscope, and the results are shown in Table 1.

[0079] High-temperature oxidation

[0080] Etched sample pieces (KO-5, 15 mm × 10 mm × 3 mm) were machined from different hot melt machines. The sample pieces were polished to 600 mesh, cleaned in ethanol / acetone and distilled water, and placed in a horizontal tube furnace, where they were exposed to temperatures ranging from 500°C to 900°C for up to 500 hours in a well-controlled simulated air atmosphere (with 2.5% water vapor by volume).

[0081] Samples were removed from the furnace after 24 h, 48 h, 96 h, 192 h, and 500 h for gravimetric analysis. Gravimetric data were collected on a Sartorius balance with an accuracy of five decimal places.

[0082] Figures 1a and 1b show the mass change (g / m³) as a function of time at different temperatures. 2 ). For example, from Figure 1b As can be seen, the comparative sample (840, 841, 843) with high ferrite content and low alumina content is losing its ability to form a protective alumina layer, as can be seen from the increase in mass change. The comparative example (961) with high ferrite content and high Al content, as well as the sample of the present invention, performed well at 800°C.

[0083] Figure 1b As shown, only the sample of this invention exhibited good oxidation performance at 900°C. Therefore, the combination of ferrite content and alumina content is crucial for obtaining excellent oxidation performance in these temperature ranges.

[0084] Mechanical testing

[0085] The yield strength of the samples (953, 954, 958) of this invention under annealing and aging conditions was measured according to standard ISO 6892-1, and the results are shown below. Figure 2 It is clear that aging the samples within the temperature range of 650℃ to 850℃ increases the yield strength. This strengthening mechanism is likely due to the formation of nickel-aluminate compounds during aging.

[0086] Therefore, it is evident that the alumina-forming austenitic-ferritic stainless steel alloy of the present invention exhibits excellent oxidation resistance in the temperature range of 500 to 900°C, and also possesses good mechanical properties.

[0087] Table 1 Fourteen alumina-forming austenitic-ferritic stainless steel hot melts are shown. These values ​​are expressed in terms of weight. The content is expressed as a percentage by volume, with the balance being Fe and unavoidable impurities, excluding ferrite. Values ​​are indicated as a percentage by volume. "The hot melt is more" Comparative hot melt.

[0088]

[0089] Table 1 (continued)

Claims

1. An alumina-forming austenitic-ferritic stainless steel, comprising the following weight percent composition: Cr 11.0 to 16.0; Ni 11.5 to 15.0; Al 3.5 to 5.0; C 0.01 to 0.15; Nb 0.01 to 2.0; Mn 0.01 to 3.2; Si 0.01 to 0.8; Cu 0 to 5.5; Zr 0 to 0.3; Mo+W 0 to 3.0; The maximum optional level is 0.1% by weight of one or more elements selected from the group consisting of rare earth metals (REM); The balance consists of Fe and commonly present impurities; and The austenitic-ferritic stainless steel described therein has a microstructure comprising more than 15% by volume and less than 45% by volume of ferrite, with the remainder being austenite.

2. The austenitic-ferritic stainless steel alloy according to claim 1, wherein the composition comprises 0.5 to 5.5% by weight of Cu.

3. The austenitic-ferritic stainless steel alloy according to claim 1 or 2, wherein the composition comprises 0.05 to 0.3% by weight of Zr.

4. The austenitic-ferritic stainless steel alloy according to claim 1 or 2, wherein the composition comprises 0.05 to 1.6% by weight of Nb.

5. A method for manufacturing an austenitic-ferritic stainless steel object, the method comprising the following steps: a) Providing an alumina-forming austenitic-ferritic stainless steel melt having the composition according to any one of claims 1 to 4; b) Cool the alumina-forming austenitic-ferritic stainless steel melt into a solid; c) Heat-process the solid into a workpiece of a predetermined shape at a temperature between 1000 and 1300°C; d) Heat-treat the workpiece at a temperature between 1050°C and 1200°C for approximately 2 to 120 minutes; e) Quench the heat-treated workpiece to room temperature.

6. The method according to claim 5 further includes a cold working step following the hot working step c).

7. The method according to claim 5 or 6, further comprising an aging step following the quenching step e).

8. An article comprising an alumina-forming austenitic-ferritic stainless steel manufactured according to any one of claims 1 to 4 or any one of claims 1 to 7.

9. Use of the object according to claim 8 in applications where the product is subjected to temperatures in the range of 500-900°C.